HUBUNGAN ANTARA KARAKTERISTIK PEKERJA DENGAN KEJADIAN STRES KERJA PADA PEKERJA KONTRUKSI PEMBUATAN HOTEL - I Kadek Dwi Arta Saputra,; Cokorda Gde Putra Pemayun,; Ni Putu Indah Rosita,; Ni Rai Sintya Agustini,; I Wayan Septa Wijaya, (Juremi: Jurnal Riset Ekonomi, 2024)
Work stress can trigger work fatigue in workers which has an impact on decreasing work productivity. This research is a quantitative descriptive research with a cross-sectional approach. The sampling technique in the study was simple random sampling. The population in this study amounted to 459 respondents and based on the calculation of the sample size formula, the sample needed was 69 respondents. To find out the incidence of stress due to work is carried out using questionnaires. The results of occupational stress events in construction workers showed that as many as 23.2% of respondents experienced work-related stress. The results of the chis quare test showed that occupational stress disorders in response had significant differences (p < 0.05) in workload and age, while other variables such as length of work and noise perception did not show significant differences with occupational stress events. Based on the findings above, the advice should be for companies to provide clear information about rest periods and targets to be achieved so that workers do not feel exhausted and burdened at work